Education and female entrepreneurship in Asia : public policies and private practices - Maslak, Mary Ann (New York, NY : Palgrave Macmillan, 2018)
"This book examines policies and practices that relate to the education of female entrepreneurs in China, India, Singapore, Indonesia, and Japan. Through both textual and interview data, the book reveals the importance of initiatives that structure entrepreneurships for women, and informal learning through networks in a variety of settings which promotes their understandings of business. Part I offers an overview of the formal and informal sectors of the economy and the international development plans related to each. Part II proffers national development plans and business policies related to female entrepreneurship in each of the five countries. Part III provides stakeholders' perspectives of entrepreneurial learning in each country. Part IV presents conceptual and theoretical models which offer a visual representation of entrepreneurs' learning process. Finally, Part V grapples with the inclusion of informal learning and networking experiences for female entrepreneurs."--
Preface; Acknowledgements; Contents; Abbreviations; List of Figures; Chapter 1 Introduction to the Book; The Field of Female Entrepreneurship: Definitions and Its Development; Bibliography; Part I Economies and Documents; Chapter 2 The Formal and Informal Economies: Setting the Stage for Female Entrepreneurship in Asia; The Sectors; Bibliography; Chapter 3 Global Initiatives for Female Entrepreneurship: The Sustainable Development and Millennium Development Goals; Sustainable Development Goals (SDGs); The Global Entrepreneurship Monitor (GEM), the Formal Sector, and International Goals; The Global Entrepreneurship Monitor (GEM), the Informal Sector, and International GoalsBibliography; Part II Country-Level Initiatives; Chapter 4 Country-Level Initiatives: China's Reflections on and Plan for Women's Entrepreneurship; Economic Outlook; Challenges Facing Female Entrepreneurs in China's Economy; Policies and Plans that Address Women's Rights; Bibliography; Chapter 5 Country-Level Initiatives: India's Reflections on and Plan for Women's Entrepreneurship; Financial Support; Educational Support; Human Resource Support; Linking the Government with Non-Governmental Organizations; Chapter 8 Country-Level Initiatives: Singapore's Reflections on and Plan for Women's EntrepreneurshipSingapore's Approach to Policy Development for Entrepreneurs: Technology; Spring; Bibliography; Part III Case Studies; Chapter 9 Women Learning About Entrepreneurship: The Case of China; The Setting; CX: Chemical Engineer; Learning on the Job; Learning in Graduate School; Learning from Life: School; Learning from Others; My Husband and Myself; My Professor; Learning from Resources; LR: Literature Review Company; Learning on the Job; Learning from Others: My Mother; XM: Mobile Telephone Franchise OwnerLearning from Life; Learning from Others: Friends and Professionals; Learning on the Job; Julie: Women's Boutique Owner; Learning on the Job; Learning from Others; Learning from Others: Friends and Family; Lady #1 and Lady #2: Hawkers; Learning from Others; HE: Esthetic Shops Owner; Learning on the Job: My Shop; Learning from Life: Continuing Education; Learning on the Job; Learning from Others: Continuing Education; HS, 3D Technology School; Learning from Others; Learning from Others: The Government; Learning from Others: The Resource Center.
Keywords: Businesswomen -- Asia; Women -- Education -- Asia; Asia -- Economic policy